2013
DOI: 10.1007/s12522-013-0147-z
|View full text |Cite
|
Sign up to set email alerts
|

Difference in mitochondrial gene expression in granulosa cells between recombinant FSH and hMG cycles under in vitro fertilization and transfer

Abstract: Purpose Examination of the mitochondrial mRNA expression in granulosa cells from an unspecified population of infertile patients to evaluate whether recombinant follicle stimulating hormone (recFSH) is more effective in producing higher quality embryo rates compared with human menopausal gonadotropin (hMG). Method Thirty-nine patients who underwent the in vitro fertilization and embryo transfer program were retrospectively examined. Patients were administered recFSH (n = 18) or hMG (n = 20) in a long protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Recently, the Cochrane Collaboration group reported moderate evidence of increased ongoing pregnancy rates after LH-containing gonadotrophin stimulation when compared to FSH-only cycles ( Mochtar et al , 2017 ). Mitochondrial gene expression data in granulosa cells support these findings: Saito et al (2013) demonstrated higher gene expression ratios and improved rates of high-quality embryos in women undergoing LH-containing stimulation with hMG when compared to a recombinant FSH regimen. While younger women may still be able to cope with such unfavorable conditions, older women, with an already somewhat compromised follicular competence, will not.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, the Cochrane Collaboration group reported moderate evidence of increased ongoing pregnancy rates after LH-containing gonadotrophin stimulation when compared to FSH-only cycles ( Mochtar et al , 2017 ). Mitochondrial gene expression data in granulosa cells support these findings: Saito et al (2013) demonstrated higher gene expression ratios and improved rates of high-quality embryos in women undergoing LH-containing stimulation with hMG when compared to a recombinant FSH regimen. While younger women may still be able to cope with such unfavorable conditions, older women, with an already somewhat compromised follicular competence, will not.…”
Section: Discussionmentioning
confidence: 63%
“…High total FSH dosage in women ≤38 years old has been shown to negatively impact subsequent embryo quality and blastocyst formation rate [26]. In contrast, the FSH dosage had no impact on the mitochondrial expression of a polycistronic RNA transcript in GCs of IVF patients [27].…”
Section: Discussionmentioning
confidence: 99%